1985
DOI: 10.1007/bf00320046
|View full text |Cite
|
Sign up to set email alerts
|

Tn polyagglutinability occurring in a patient with B cell lymphoma

Abstract: A case of polymorphic immunocytoma (B cell lymphoma) coinciding with expression of Tn antigen on a population of erythrocytes is presented. Tn activation was found incidentally by screening blood samples of patients suffering from hematologic malignancies with a Tn specific lectin from Salvia sclarea. So far, Tn activation has been reported only in apparently healthy subjects or in subjects suffering from or developing myeloid leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…One mechanism for Tn antigen expression was found to be genetic mutations of Cosmc (6, 19, 20), or lossof-heterozygosity, in Cosmc (19). Our finding that Cosmc is epi-genetically silenced in Tn4 cells may be related to studies of Tn antigen expression in human leukemic cells, such as myeloma (44), lymphoma (45), and chronic lymphocytic leukemia (46). Aller et al (46) reported that the B cells from six of six patients with B-cell chronic lymphocytic leukemia were Tn-positive, whereas the blood cells from five normal individuals were negative for Tn expression.…”
Section: Discussionmentioning
confidence: 59%
“…One mechanism for Tn antigen expression was found to be genetic mutations of Cosmc (6, 19, 20), or lossof-heterozygosity, in Cosmc (19). Our finding that Cosmc is epi-genetically silenced in Tn4 cells may be related to studies of Tn antigen expression in human leukemic cells, such as myeloma (44), lymphoma (45), and chronic lymphocytic leukemia (46). Aller et al (46) reported that the B cells from six of six patients with B-cell chronic lymphocytic leukemia were Tn-positive, whereas the blood cells from five normal individuals were negative for Tn expression.…”
Section: Discussionmentioning
confidence: 59%
“…In patient R.R., 93% of erythrocytes were deficient in (33Gal-T activity. Exposed Tn antigen as a result of this deficiency is recognized by natural antibodies present in most human adult sera [38]. Moreover, Tnf cells may represent an additional antigenic stimulus that triggers the autoimmune response to Tn epitope-presenting cells resulting in hematologic abnormalities including mild hemolysis and moderate thrombopenia in patient R.R.…”
Section: Discussionmentioning
confidence: 99%
“…These patients, who are also said to have blood group Tn (5), occasionally develop hemolytic anemia, thrombopenia, and leukopenia most likely mediated by anti-Tn natural antibodies present in normal serum (6). Tn polyagglutinability has been observed in the context of hemoproliferative disorders (7) and Tn antigen expression may also accompany malignant transformation (8). The enzyme deficiency was thought to arise from a somatic stem cell mutation resulting in the clonal penetration ofTn antigen-expressing cells into the various hematopoietic lineages (9).…”
Section: Introductionmentioning
confidence: 99%